2015
DOI: 10.12738/estp.2015.3.2436
|View full text |Cite
|
Sign up to set email alerts
|

Personality Traits and Positive/Negative Affects: An Analysis of Meaning in Life among Adults

Abstract: This study examines the impact of positive and negative affects and personality traits on meaning in life in an adult population. The sample consisted of 335 subjects: 190 females and 145 males, and a Meaning in Life Questionnaire (MLQ), positive and negative schedule (PANAS), and adjective-based personality scale (ABPT) were used in the research. The data were analyzed on a one-way analysis of variance (ANOVA) as well as a Pearson product moment correlation and hierarchical multiple regression analysis. Accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…On the other hand, NA was also positively and significantly associated with the two subscales of PIL. Previous studies have found that the purpose of life has been related to greater well-being (e.g., Işik and Üzbe, 2015), more positive affect, and less negative affect. However, it is suggested that psychological interventions aimed at re-signifying experiences and finding new meaning in their lives could help to cushion the negative effects of the pandemic situation.…”
Section: Discussionmentioning
confidence: 96%
“…On the other hand, NA was also positively and significantly associated with the two subscales of PIL. Previous studies have found that the purpose of life has been related to greater well-being (e.g., Işik and Üzbe, 2015), more positive affect, and less negative affect. However, it is suggested that psychological interventions aimed at re-signifying experiences and finding new meaning in their lives could help to cushion the negative effects of the pandemic situation.…”
Section: Discussionmentioning
confidence: 96%
“…However, the lack of relation with EWB is not in line with those research findings. Again, it might be that threats influence emotional well-being through negative affects only, as it has been demonstrated that positive and negative affect are distinct dimensions with different correlates (Diener and Emmons, 1984;Raufaste and Vautier, 2008;Işik and Üzbe, 2015). The construct of emotional wellbeing would have been captured more comprehensively if we had incorporated such a dimension.…”
Section: The Protective Roles Of Psychological Resourcesmentioning
confidence: 99%
“…There have been studies done with different age stages, based on the assumption that meaning may change with age (Reker, 2005;. In a study from Turkey, however, the presence of meaning showed no meaningful difference between age stages, while the source of meaning actually diminished (Işık & Üzbe, 2015). In another study, affective meaning displays no difference between young and older people; whereas the cognitive meaning appears to increase with age (Scannell, Allen, & Burton, 2002).…”
Section: Present Studymentioning
confidence: 99%